Malaria burden and case management in the Republic of Congo: limited use and application of rapid diagnostic tests results - Ntoumi, Francine (BioMed Central, 2013)
BACKGROUND: There have been few investigations evaluating the burden of malaria disease at district level in the Republic of Congo since the introduction of artemisinin-based combination therapies (ACTs). The main objective of this study was to document laboratory-confirmed cases of malaria using microscopy and/or rapid diagnostic tests (RDTs) in children and pregnant women attending selected health facilities in Brazzaville and Pointe Noire, the two main cities of the country. Secondly, P. falciparum genetic diversity and multiplicity of infection during the malaria transmission season of October 2011 to February 2012 in these areas were described. METHODS: Three and one health facilities were selected in Brazzaville and Pointe-Noire as sentinel sites for malaria surveillance. Children under 15 years of age and pregnant women were enrolled if study criteria were met and lab technicians used RDT and/or microscopy to diagnose malaria. In order to determine the multiplicity of infection, parasite DNA was extracted from RDT cassette and msp2 P.falciparum genotyped. RESULTS: Malaria prevalence among more than 3,000 children and 700 pregnant women ranged from 8 to 29%, and 8 to 24% respectively depending on health center locality. While health workers did not optimize use of RDTs, microscopy remained a reference diagnostic tool. Quality control of malaria diagnosis at the reference laboratory showed acceptable health centre performances. P. falciparum genetic diversity determination using msp2 gene marker ranged from 9 to 20 alleles and remains stable while multiplicity of infection (mean of 1.7clone/infected individual) and parasite densities in clinical isolates were lower than previously reported. CONCLUSIONS: These findings are consistent with a reduction of malaria transmission in the two areas. This study raises the issue of targeted training for health workers and sustained availability of RDTs in order to improve quality of care through optimal use of RDTs.